1990
DOI: 10.1111/j.1365-2389.1990.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of soil aggregates in relation to organic constituents and soil water content

Abstract: The effects of soil organic matter content, soil water content and duration of wet-sieving on aggregate stability of soils with contrasting cropping histories were investigated. Longterm pasture samples had a greater aggregate stability than long-term arable samples. However, air-drying aggregates before wet-sieving increased the aggregate stability of long-term pasture samples, but decreased that of long-term arable samples. With increasing duration of wet-sieving, the proportion of water-stable aggregates de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
159
3
14

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(188 citation statements)
references
References 18 publications
12
159
3
14
Order By: Relevance
“…O manejo, o uso e o tempo de utilização promovem diversas alterações nas propriedades do solo, como por exemplo, na estrutura, que está relacionada à agregação. A matéria orgânica é um dos principais agentes de formação e estabilização de agregados, e a diminuição de seu conteúdo no solo pelo cultivo é uma das maiores causas de deterioração da estrutura do solo (Haynes & Swift, 1990;Wendling …”
Section: Introductionunclassified
“…O manejo, o uso e o tempo de utilização promovem diversas alterações nas propriedades do solo, como por exemplo, na estrutura, que está relacionada à agregação. A matéria orgânica é um dos principais agentes de formação e estabilização de agregados, e a diminuição de seu conteúdo no solo pelo cultivo é uma das maiores causas de deterioração da estrutura do solo (Haynes & Swift, 1990;Wendling …”
Section: Introductionunclassified
“…Haynes and Swift (1990) (Tisdall and Oades 1979;Jastrow 1987). The involvement of the aliphatic fraction in the stabilization of soil macroaggregates was also suggested (Capriel et al 1990 performed with an apparatus similar to that described by Bourget and Kemp (1957) An analysis of variance for split-plot was used to determine the significance of the rotation and tillage effects, and the date effect was analyzed using the univariate repeated-measure approach (Freund et al 1986).…”
mentioning
confidence: 99%
“…The hot-water extractable pool is probably dominated by mucigel of microbial origin (6,25). The monosaccharide composition of microbial carbohydrates clearly differs from that of plant material; microorganisms produce predominantly galactose (G) and mannose (M), while plant tissue and root mucigels are the major sources of arabinose (A) and xylose (X) (26,27).…”
Section: Reprintsmentioning
confidence: 99%
“…In both soils the carbohydrate C content was lowest in the 4.0-8.0 mm fraction. Several longterm studies have shown that rotation with legumes can increase the amount of carbohydrates in soil (6,10,18). Soil carbohydrates were strongly influenced by soil management systems, including amendments with bark compost or leaf litter (19).…”
Section: Carbohydrates and Soil Aggregates 629mentioning
confidence: 99%
See 1 more Smart Citation